Determining Procurement Strategy Alternatives Through The Identification And Assessment Of Delay Risks In Procurement Activities For Public School Construction Projects In DKI Jakarta Province - Boris Sembiring Kembaren Boris; Ayomi Dita Rarasati; Wisnu Isvara (CV. AFDIFAL MAJU BERKAH, 2026)
Public school building construction projects in DKI Jakarta Province are one of the government’s strategic programs to improve the quality of educational facilities. In their implementation, the construction procurement process plays an important role in determining project success, particularly in terms of timely completion. However, various activities within the procurement process have the potential to create delay risks that may affect overall project performance. This study aims to identify activities in the construction procurement process that have the potential to cause delays and to assess delay risks based on two main dimensions, namely risk impact and likelihood of occurrence. The research method used is descriptive qualitative with a case study approach. Data collection techniques include observation, survey (Likert-scale questionnaire), document study, and archive analysis. The research respondents consist of parties directly involved in the construction procurement process. Data analysis is conducted using descriptive qualitative analysis and risk analysis to determine the level of risk for each procurement activity. The results of this study are expected to provide an overview of critical activities in the procurement process that have the potential to cause delays and serve as a basis for improving construction procurement management in public school building projects in DKI Jakarta Province. Based on the results of the risk analysis, the highest-risk factors are identified and selected, and procurement strategies are then formulated to minimize the risk of delays in public school building construction projects in DKI Jakarta Province.